Pelatihan Penyusunan dan Pengelolaan Prosedur Berbasis Risiko: Upaya Identifikasi Aspek Risiko dalam Prosedur Organisasi - Sitepu, Hans Victor; Setiawati, Novilia; Pratiwi, Eliza Septiani; Damarsari, Errica (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2026)
Every organization will require good procedures and systems in order to achieve its goals. Procedures provide consistent standards for each individual to follow in carrying out their obligations correctly and uniformly. Risk-based procedures are increasingly being adopted by organizations across industries to increase operational efficiency and regulatory compliance. To improve the organization's quality, PT Arsya Yasa Indonesia hosted a two-day training activity on the Preparation and Management of Risk-Based Procedures, with the author serving as the material provider. The author's experience in implementing quality management and risk management can support Accounting Information Systems and Management Information Systems in a variety of companies and industries. The author explains to the participants using three methods: the Lecture Method, the Question-and-Answer Method, and the Case Study Discussion and Discussion Method, all of which are conducted online. This training activity allows participants to gain a better understanding of the concept and application of Risk-Based Procedure Preparation and Management, as well as skills in using various types of risk management tools and techniques to integrate into the procedure preparation process in their respective workplaces. According to the results of the post-activity interview, all the training participants were satisfied with the training results and his team's absorption of the content